Anthropometric and physical profiles of English academy rugby union players - Darrall-Jones, J. D.; Jones, B.; Till, K. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to evaluate the anthropometric and physical characteristics of English regional academy rugby union players by age category (under 16s, under 18s and under 21s). Data were collected on 67 academy players at the beginning of the preseason period and comprised anthropometric (height, body mass, and sum of 8 skinfolds) and physical (5-, 10-, 20-, and 40-m sprint, acceleration, velocity, and momentum; agility 505; vertical jump; Yo-Yo intermittent recovery test level 1; 30-15 intermittent fitness test; absolute and relative 3 repetition maximum front squat, split squat, bench press, prone row, and chin; and isometric mid-thigh pull). One-way analysis of variance demonstrated significant increases across the 3 age categories (p = 0.05) for height (e.g., 16s = 178.8 ± 7.1; 18s = 183.5 ± 7.2; 21s = 186.7 ± 6.61 cm), body mass (e.g., 16s = 79.4 ± 12.8; 18s = 88.3 ± 11.9; 21s = 98.3 ± 10.4 kg), countermovement jump height and peak power, sprint momentum, velocity, and acceleration; absolute, relative, and isometric (e.g., 16s = 2,157.9 ± 309.9; 18s = 2,561.3 ± 339.4; 21s = 3,104.5 ± 354.0 N) strength. Momentum, maximal speed, and the ability to maintain acceleration were all discriminating factors between age categories, suggesting that these variables may be more important to monitor rather than sprint times. These findings highlight that anthropometric and physical characteristics develop across age categories and provide comparative data for English Academy Rugby Union players.